Pirólise lenta de serragem de eucalipto para obtenção de bioóleo e carvão - Cardoso, André de Lima (2004)
This dissertation presents the slow pyrolysis of eucalyptus sawdust as an alternative, thermal process of treatment of forestry residues for the obtainment of gaseous, liquid and solid products. With the aid of a pyrolysis oven and low temperature conversion of the biomass residue, four product fractions were obtained in batch procedure: one gaseous (F1), two liquids - aqueous (F2) e bio oil (F3) and one solid (F4, char). Parameters like temperature, heating rate and particle size and theirs effects over the process yield were studied. liquid and solid products were submitted to analytical methods of characterization: for the aqueous and the bio oil fractions, the elemental composition, moisture, solubility, qualitative composition by gas chromatography/mass spectrometry detection (GC-MS), spectroscopic figures (infrared, ultraviolet e nuclear magnetic resonance), high heating power and acute toxicity, were measured. The residual char was although submitted to proximate analysis, scanning electron microscopy (SEM), spectroscopic analysis (infrared and X-ray diffraction), superficial area analysis (BET), adsorption (dye and carbohydrate adsorption) and high heating value tests. The liquid fractions showed themselves as potential sources of input chemicals, particularly, of phenolic substances. The residual char, even not activated, showed considerable adsorption capacity. The developed low pyrolysis process demonstrated to be efficient, generating at least two fractions of great industrial interest: bio oil, fuel oil substitute and diesel oil addictive and input chemicals source; and char, precursor of industrial adsorbent and clean solid fuel.